Atenuação e imunogenicidade de uma cepa recombinante do herpesvírus bovino tipo 5 defectiva na glicoproteína e e enzima timidina quinase - Anziliero, Deniz (2010)
The present study describes an investigation of the attenuation/virulence and immunogenicity of a recombinant BoHV-5, a candidate vaccine strain. The recombinant BoHV-5gE/TKΔ was constructed out of a Brazilian BoHV-5 strain (SV507/99) and contains deletions in glycoprotein E (gE) gene as antigenic marker - and thymidine kinase (TK) gene for attenuation. In Chapter 1, we investigated the attenuation and immunogenicity of the recombinant in calves. Eighty-to-ninety days old calves (n=6) inoculated intranasally (IN) with the recombinant virus (titer of 107.5 TCID50) showed no clinical signs, and shed low titers of virus in nasal secretions. On day 30 post-infection (pi), all animals had neutralizing antibodies against BoHV-5, in titers from 4 to 8 and remained negative for antibodies to gE. Administration of dexamethasone (Dx) to four of these calves at day 42 pi (0.1mg/kg/day during 5 days) did not result in virus shedding or increase in antibody titers, indicating lack of viral reactivation. In a second experiment, intramuscular immunization (IM) of calves with 8 months of age (n=9) with the recombinant virus (107.5 TCID50/animal) did not result in virus shedding or clinical signs. Vaccinated animals developed neutralizing antibodies in titers from 2 to 8 at day 42 post-vaccination (PV) and remained negative for gE antibodies. Finally, 21 calves (approximately 10 months old) were vaccinated IM with the recombinant virus (107.3 TCID50). All vaccinated animals developed neutralizing antibodies in titers from 2 to 16 at day 30pv. A boost vaccination performed on those animals at day 240 pv resulted in a rapid and strong anamnestic antibody response, with VN titers reaching from 16 to 256 at day 14 post-booster. Serum samples of all animals remained negative for gE antibodies. Serum samples from vaccinated animals showed cross-neutralizing activity against nine field isolates of BoHV-5 and eight of BoHV-1. Chapter 2 describes an investigation of the immunogenicity and protection conferred by the recombinant virus against homologous (BoHV-5) and heterologous challenge (BoHV-1). A group of nine calves seronegative for BoHV-5 were vaccinated IM in a dose of 107.5 TCID50 of the recombinant virus and eight animals were maintained as non vaccinated controls. All vaccinated animals seroconverted 14 days postvaccination (pv), with neutralizing antibody titers from 2 to 4. At day 42 post-vaccination (pv), the vaccinated animals and controls were challenged by IN instillation of BoHV-5 or BoHV-1 isolates. After challenge, the length and magnitude of virus shedding was reduced in vaccinated animals compared to controls in both groups (challenged with BoHV-1 and BoHV-5). The vaccinated animals did not show systemic, respiratory or neurological clinical signs after challenge. Furthermore, the control animals challenged with BoHV-5 (n=4) developed severe neurological disease and were euthanized in extremis between days 13 and 14 post-challenge (pd). The challenge resulted in a strong and rapid anamnestic response in vaccinated animals, inducing neutralizing titers higher than in control animals. Antibodies to gE were detected only after challenge in both vaccinated and controls calves. These results indicate that recombinant BoHV-5 gE/TKΔ is an adequate candidate for a vaccine strain, with an antigenic marker, since it is attenuated and immunogenic for calves and provides homologous and heterologous (BoHV-1) protection.